(untitled) (Research, Society and Development, 2020)
This research aimed to verify the level of knowledge of pregnant women about the function of the pelvic floor and the importance of sexuality during pregnancy. Descriptive exploratory cross-sectional study with a quantitative approach. The sample included 27 pregnant women in a Basic Health Unit in the city of Caxias, Maranhão. Data were collected in March 2018, of these, 48% are between 21-30 years old, 33% 18-20 years old, 63% work at home, 48% have completed high school, 37% only elementary school and 52% are married, 41% were in the 3rd trimester of pregnancy, 37% in the 2nd trimester and 22% in the 1st trimester, 93% never even heard about the pelvic floor or knew about the importance of the perineum for women’s health, 89% reported not knowing what is the perineum and 85% were unaware of the location of the perineum, 70% reported having an active sexual life during pregnancy, 59% know the importance of the act during pregnancy and 78% stated that having sex during pregnancy helps in labor, 85% recognize that sexual intercourse during pregnancy does not harm the baby. There is a considerable lack of information regarding the knowledge, function and importance of the pelvic and perineum floor for pregnancy. It is essential that initiatives are taken that seek to inform women about such points, body awareness at this stage can lead to quality of life for pregnant women.